Computational analysis of a sandwich shield with free boundary inserted fabric at high velocity impact. (4th May 2017) - Moon, Jin Bum; Park, Yurim; Son, Gilsang; Kim, Chun-Gon
Abstract : In this paper, a novel hybrid composite shield to protect space structures from hypervelocity impact of micrometeoroid and space debris is proposed. The finite-element model of the proposed shield was constructed and finite-element analysis was conducted to approximate the energy absorption rate. Before the final model analysis, analysis of each component including the aluminum plate (front plate), PMMA plate (rear plate), and intermediate layer of fabric was performed, verifying the finite-element model of each component. The material properties used in the analysis were predicted material property values for high strain rates. The analysis results showed that, other than the fabric, the energy absorption rate of each component was in agreement. Afterwards, the finite-element model of the hybrid composite shield was constructed, where it was analyzed for the constrained and unconstrained fabric boundary condition cases. Through the finite-element analysis, the fiber pullout mechanism was realized for the hybrid shield with free boundary inserted fabric, and it was observed that this mechanism led to energy absorption increase.